A knowledge, attitude and practice (KAP) study on physical wellness of University Technology MARA academic staff a case study in Shah Alam Campus / Mangalam K.S. Gopala Iyer … [et al.] - K.S. Gopala Iyer, Mangalam; Haron, Halilah; Mohd Zaid, Rohani; Abdul Kadir, Zulkifli (2006)
This study was done to determine the level of physical wellness among the academic staff of University Teknologi Mara (UiTM). Physical wellness was measured using five components: work; spiritual; health condition and physical activities; emotional and mental outlook and; leisure and social activities. The study also examined whether the components of knowledge, attitude and practice had any impact on the level of wellness experienced by these academicians. A sample of 404 academicians was selected randomly from all faculties at the Shah Alam, Puncak Perdana, Section 17, Shah Alam and Jalan Othman campuses. Questionnaires were self-administered to these academicians and a total of 325 academicians responded. An overwhelming 93% of the academicians rated their health as good, very good or excellent. About 63% of them were confident most of the time and only 4% were upset most of the time. Majority of the academicians experienced a low to medium level of physical wellness. The study revealed that while the components of attitude and practice affected the level of wellness, knowledge had no impact on the wellness of the academicians.